WAIS Divide Replicate Core Methane Isotopic Data Set - Brook, Edward J. (IEDA: US Antarctic Program Data Center, 2017)
Data set contains stable isotope data set for methane in the WAIS Divide replicate core for the interval of 3009 to 2071 meters. These measurements were made by James Lee at the University of Bern as part of his PhD thesis and are the subject of a paper in preparation.